“This was the highlight of our trip!” What can TripAdvisor reviews teach us about the tourism experience? - Guðný Ljósbrá Hreinsdóttir 1994- (2022)
Food tours have become a popular leisure activity for tourists who want to experience their destination uniquely and interactively. Located in Iceland, one food tour has the most excellent five-star reviews out of any food tour currently on TripAdvisor. This empirical study aimed to identify what factors make up a successful food tourism experience. To do so all TripAdvisor reviews from The Reykjavík Food Walk written in the year 2021 were analysed with the use of social media analytics and content analysis. Out of the 524 reviews analysed seven main factors were identified that led to the enhancement of the food walk experience, those factors were; food experience, guide experience, enjoyment experience, environment experience, informative, recommend doing early, and returned to restaurants. Most of the reviewers were women from the US. Findings from this study showed the guide to be the most valuable attribute in a successful food walk experience, in line with previous research on the subject. This study shows how consumer-generated content can be utilized to further improve marketing and service efforts within the food tourism industry and gives ideas for further marketing efforts and future research on the matter. These findings also help shape and give an understanding of the tourism experience.